ANALISIS HASIL BELAJAR DAN SIKAP TERHADAP PENYALAHGUNAAN PSIKOTROPIKA DAN ZAT ADIKTIF PADA PEMBELAJARAN SISTEM SARAF DENGAN BIOEDUTAINMENT ROLE PLAY PADA SISWA SMA - Lisdiana, Lisdiana; Saptono, Sigit; Ismarlini, Ismarlini (Indonesian Journal of Conservation, 2017)
This study would analyze students’ learning outcomes and attitudes on psychotropic and addictive substances abuse after learning the nervous system concept with bio edutainment strategy by roleplaying. This was a pre-experimental study with one group pretest-posttest design. The population in this study was all students of class XI of Sciences program in SMA Negeri 7 Semarang. Two classes as the sample which was defined by purposive sampling. The independent variable was bio edutainment strategy with role-playing. The dependent variables were students’ learning outcomes and attitudes. The controls variables included teacher, lesson hours, curriculum, and face-to-face time. Learning outcomes were analyzed quantitatively by N-gain. Students’ attitudes were analyzed descriptively. The learning outcomes had met the classroom learning mastery (86.5%). The means of N-gain in both classes were in moderate criteria (0.44 and 0.40). Student attitudes toward psychotropic and addictive substances abuse were in tremendous criteria (92% and 86%). Students’ learning outcomes were strongly correlated with their attitudes toward psychotropic and addictive substances abuse (0.705 and 0.610). This study concluded that bio edutainment strategy with roleplaying gave a positive effect on students’ learning outcomes and attitudes and a positive relationship between high school students’ learning outcomes and their attitudes on psychotropic and addictive substances abuse.Penelitian ini bertujuan untuk menganalisis hasil belajar dan sikap terhadap penyalahgunaan psikotropika dan zat adiktif pada siswa setelah pembelajaran system saraf dengan strategi bioedutainment dengan role playing. Penelitian ini menggunakan rancangan pre-eksperimental design dengan one group pretest-posttest. Populasi dalam penelitian ini yaitu seluruh siswa kelas XI IPA SMA Negeri 7 Semarang dengan dua kelas sebagai sampel yang ditentukan secara purposive sampling. Variabel bebas berupa strategi bioedutainment dengan role playing. Variabel terikat berupa hasil belajar, dan sikap. Variabel kontrol berupa guru, jam pelajaran, kurikulum, dan waktu tatap muka. Hasil belajar dianalisis dengan N-gain dan kuantitatif. Sikap dianalisis secara deskriptif persentase. Hasil belajar mencapai ketuntasan klasikal (86,5%). Rata- rata N-gain siswa pada kedua kelas termasuk kriteria sedang (0,44 dan 0,40). Sikap siswa terhadap penyalahgunaan psikotropika dan zat adiktif menunjukkan kriteria sangat tinggi (92% dan 86%). Hasil belajar dengan sikap terhadap penyalahgunaan psikotropika dan zat adiktif memiliki korelasi kuat (0,705 dan 0,610). Simpulan strategi bioedutainment dengan role playing berpengaruh positif terhadap hasil belajar dan sikap siswa serta terdapat hubungan yang positif antara hasil belajar dengan sikap siswa terhadap penyalahgunaan psikotropika dan zat adiktif pada siswa SMA.